Study guides

Q: 2a -3 plus 4b - 2a -b -3 plus 5?

Write your answer...

Submit

Related questions

2a-3+4b-2a-b-2a-b-3+5 Can be simplified to: 3b-1

2a + 4b - 52a + 4b - 52a + 4b - 52a + 4b - 5

3b -1

3a + 4b - 5 - 1a + 7b + 3 - 1b 2a + 10b - 5 + 3 2a + 10b - 2

2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1

(6a3 - 19a2 + 15a)/(2a - 3) = a(6a2 - 19a + 15)/(2a - 3) = a(2a - 3)(3a -5)/(2a -3) = a(3a - 5)

9a +8 -2a -3 -5a = 2a +5

If 3a+5=5a+3, then: 3a+5 - 3a = 5a+3 - 3a 5=2a+3 5 - 3=2a+3 - 3 2=2a a=1

(a - 5)(a + 3) = a2 - 2a - 15

It is: (2*3)+5 = 11

2a-5

2a+5a=3 7a=3 a=3/7 or .4286

2a+5

a+b+2+3=5+a+b

a=5

Well if it is worded right then 4xb-1+(-4)+4b=4b-1-4+4b=4b+4b-1-4=8b-5

4b plus 7b plus 5 will equal 11b plus 5. When you have two variables that are the same you can add the two numbers with the variables remaining the same.

12(8a + 28) + 2a + 5 84a + 336 + 2a + 5 86a + 341

its a quadratic equation. (4b-5) (4b-5)

7 + 4b + 3b + 6b + 5 =7 + 13b + 5 =12 + 13b

The answer to 6b plus 7 times 5-4b plus 1 equals 38. This is taught in math.

Not sure why it is 3a2- if you mean 3*a*2, then: 3*a*2=6a (6a-2a)+5-2(a (or a2)+a)=1 4a+5-(2a+a)=1 4a+5-2a-a=1 Then take the 5 over (remember, the +5 become -5 when transposed): 4a-2a-a=1-5 Solving the equations on both sides gives: a=-4 Is this your answer?

Start with simplifying: 2a + -3 = 5 and reordering: -3 + 2a = 5. Then add '3' to each side of the equation: -3 + 3 + 2a = 5 + 3 and you get 2a = 8 once all like terms are combined. The last step is to divide both sides by 2 and you get the answer, which is a = 4.

-2b+8-4b = -5-11b+7 -2b-4b+11b = -5+7-8 5b = -6 b = -6/5

7